2021
DOI: 10.3390/nu13020299
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic Programming Effects during Lactation: A Narrative Review and Conceptual Model Focusing on Underlying Mechanisms and Promising Future Research Avenues

Abstract: Animal studies have consistently demonstrated that maternal obesity and a high-fat diet during lactation enhances obesity risk in the offspring. However, less is known about these potential obesogenic programming effects in obese humans. We propose three important pathways that may explain obesogenic programming effects of human breastmilk. First, human milk components and hormones may directly affect child eating and satiety characteristics. Second, human milk constituents can affect child microbiota that, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
(90 reference statements)
0
6
0
1
Order By: Relevance
“…In addition to the behavioral and molecular phenotypes identified in the mHFD offspring, multiple publications have reported that maternal obesity leads to aberrant feeding patterns and disturbed metabolic programming in the offspring. Such outcomes of mHFD were beyond the scope of this review as there are other comprehensive publications that have focused on this particular aspect of maternal nutrition (Chaves et al, 2021;Gawlińska et al, 2021;Larsen and Bode, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the behavioral and molecular phenotypes identified in the mHFD offspring, multiple publications have reported that maternal obesity leads to aberrant feeding patterns and disturbed metabolic programming in the offspring. Such outcomes of mHFD were beyond the scope of this review as there are other comprehensive publications that have focused on this particular aspect of maternal nutrition (Chaves et al, 2021;Gawlińska et al, 2021;Larsen and Bode, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Determinants of the breastmilk exposome include numerous physiological and behavioral maternal factors including obesity, diabetes, physical activity, diet, and psychosocial stress, as well as infant factors 124,125 . The concept that maternal obesity, diabetes, and other metabolic characteristics alters milk composition, which, via molecular mechanisms, then induce increased adiposity and risk of obesity in the child, is referred to as “lactational programming.” 126,127 Research employing rodent models suggests there are changes in milk hormones in diet‐induced obese rodent dams, which enter the offspring circulation and retain bioactivity. Offspring fed milk of obese dams have been shown to have altered neuronal development affecting appetite centers of the hypothalamus and develop metabolic syndrome traits, despite later low‐fat diets 128 .…”
Section: The Early Life Exposome: Exposures During Infancy and Early ...mentioning
confidence: 99%
“…The existing literature is hampered by significant heterogeneity between studies (for example, in the definitions of breastfeeding exclusivity and duration, as well as the timing and measurement processes for measures of adiposity) and the potential for residual confounding 3 , 8 11 . The mechanistic pathways that may link breastfeeding to protection against childhood obesity are not yet well understood 12 , but a variety of HM components, including macro- and micronutrients as well as cytokines and hormones, likely contribute to variations in growth 13 , 14 . Further, breastfeeding may directly affect feeding preferences in a manner that prevents obesogenic eating patterns 12 , and additionally, behavioral aspects of breastfeeding may help infant-mother dyads with self-regulation and attentiveness to fullness and satiety cues 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic pathways that may link breastfeeding to protection against childhood obesity are not yet well understood 12 , but a variety of HM components, including macro- and micronutrients as well as cytokines and hormones, likely contribute to variations in growth 13 , 14 . Further, breastfeeding may directly affect feeding preferences in a manner that prevents obesogenic eating patterns 12 , and additionally, behavioral aspects of breastfeeding may help infant-mother dyads with self-regulation and attentiveness to fullness and satiety cues 14 . Collectively, these effects may contribute to preventing excess or rapid weight gain in breastfed infants, leading to reduced risks of later overweight and obesity 15 17 .…”
Section: Introductionmentioning
confidence: 99%